Technical determinants of tackle and ruck performance in international rugby sevens - Hendricks, S.; Sin, D. W.; van Niekerk, T.; den Hollander, S.; Brown, J.; Maree, W.; Treu, P.; Lambert, M. (European Journal of Sport Science, 2020)
Rugby Sevens (`Sevens`) is one of the fastest growing sports in the world. This growth was marked by the inclusion of the sport in the Olympic Games in 2016. The most frequently occurring contact events in Sevens are the tackle and ruck. Performing specific techniques during these contact events can reduce the risk of injury and increase the likelihood of success. Therefore, the purpose of this study was to identify the technical determinants associated with tackle and ruck performance outcomes in Sevens. A total of 4799 tackles and 1405 rucks from the 2014/2015 HSBC Sevens World Series were coded for contact, post-contact, ruck, match contextual variables and outcomes. Relative risk ratio (RR), the ratio of the probability of an outcome occurring when a variable was observed, was determined using multinomial logistic regression. A moderate ball-carrier leg drive reduced the probability of losing possession by 25% (RR 0.75, 95% CI, 0.58-0.97, p < .05). Conversely, ball-carriers had a 53% higher likelihood of losing possession when the tackler executed a moderate leg drive (RR 1.53, 95% CI, 1.09-2.14, p = .05). Maintaining possession at the ruck was more likely to occur when committing one attacker compared to two (RR 0.31, 95% CI, 0.19-0.49, p < .001). Active ball-carrier placement also increased the likelihood of maintaining possession at the ruck (RR 14.67, 95% CI, 9.55-22.56, p < .001). Sevens coaches and trainers can now positively design evidence-based technical training programmes and emphasise specific tackle techniques in training using data from Sevens video analysis. Also, given that this is the first study to relate tackle technical determinants to an outcome (i.e. the first `how` study) in Sevens, this work provides the foundation for similar Sevens video analysis studies in the future.